PENGARUH TEKANAN KERJA (STRES) DAN PENGEMBAGAN KARIR TERHADAP KINERJA KARYAWAN Di PT SINAR PANDAWA MEDAN - M Tahir (Universitas Islam Islam Sumatera Utara, 2018)
The purpose of this study is to test and analyze the influence of work stress and career development on employee performance in PT. Sinar Pandawa which is located at Jalan Kejaksaan No.7 Medan. This study is a quantitative descriptive study and a population is 94 employees of the company. The questionnaires were used as instruments for data collection from 64 employees as samples of the study and data were analyzed by using multiple regressions whereas the analysis included normality test, heteroscedasticity test and multicollinearity test. The results of this study indicated that work stress partially affects the employees performance of PT. Sinar Pandawa-Medan and so also career development have a significant effect on employee performance. The analysis also indicated that both work stress variables and career development variables simultaneously affect the employee performance of PT Sinar Pandawa-Medan significantly.